Isolation, Screening and Growth of Monoaromatic Hydrocarbon Utilising Bacteria - Sannasi @ Sannach, Palsan (1998)
A total of 131 isolates originating from different soils were obtained through enrichment and direct plating methods using 0.1% (v/v) of either benzene, toluene or mixture of benzene and toluene as their sole energy and carbon sources. Most of the isolates were from S5 (garden soil) and the least from SI (ESSO refinery soil) obtained by the enrichment culture method. Out of this, 107 motphologicaUy different isolates were rescreened in 1% (v/v) of their respective hydrocarbon of either benzene or toluene. Out of the 34 good isolates grown in varying hydrocarbon concentrations ul> to 50% (v/v), 23 gave good and moderate growth. These isolates were further grown in different concentrations of BTEX. Six isolates (145yw, 113i, 205y, 205w, 113 & 146) exhibited good growth withstanding up to 75 % (v/v) concentration of BTEX. The isolates were also able to grow in 0.4 M NaCl (35 p.s.u.) which is equivalent to sea salinity level. Studies done on the 3 isolates (145yw, 113i & 205y) showed that they were metabolically active throughout their growth in the hydrocarbon spiked media deduced from the !NT stain test, increased oxygen consumption and increased plate COWlts. High colony fonning Wlits / mL percentage (50% or more) were obsetVed in different organic solvents of varying log P values. Isolate 145yw gave the highest growth rate of 0.22 ht in 0.1% (v/v) benzene. Biodegradability of the isolates were further confinned by positive CO2 production and the reduction in the hydrocarbon peaks obsetVed by GC. Extensive degradative profiles were obtained with isolate 113i and mixed culture. Laboratory biodegradation studies showed that all the 3 isolates were able to grow in both single and mixture of site samples.